Deliberative democracy and historical perspectives on American Indian/Alaska native political decision-making practices - Reedy, Justin (Humanit Soc Sci Commun, 2020)
Public deliberation has risen to the forefront of governance as a technique for increasing participation in policy making. Scholars and practitioners have also noted the potential for deliberation to give greater influence to historically marginalized populations, such as Indigenous peoples. However, there has been less attention paid to the potential fit between the ideals of deliberation and the governance and decision making practices of American Indian and Alaska Native (AI/AN) peoples. In this paper, we begin to address this gap by analyzing accounts of AI/AN governance from the perspective of deliberation, and note areas of overlap, synergy, and conflict. We conduct a close reading of key historical and ethnographic accounts of four historical AI/AN contexts—the Iroquois Confederation under the Great Law of Peace, 19th century accounts of the Ojibwa village, the Santa Clara Pueblo government in pre-19th century, and Yup’ik village life in the early 20th century—and a more contemporary case in the form of the Santa Clara Pueblo’s Constitution from the Indian Reorganization Act period. We then apply two sets of key criteria for deliberative democracy—from the scholars Robert Dahl and John Gastil—to these accounts and note the ways in which each system is or is not congruent with these frameworks of deliberation. We find variations between these historical tribal contexts in our analysis. Social components of deliberation, such as respectful discussion and equal opportunities to participate, were partially or fully present in many accounts of governance practices, but it was less clear whether the analytic components, such as discussion of a range of solutions, were included in some forms of tribal governance. We then explore the potential implications of our findings for public deliberation within and in AI/AN tribes. We note that deliberative scholars and practitioners should be wary of over-generalizing about AI/AN tribes.